A maximum likelihood estimation approach for spliced distributions obtained through quantile splicing - Otieno Mac'Oduol, Brenda (University of Pretoria, 2023)
Mini Dissertation (MSc (Advanced Data Analytics))--University of Pretoria, 2022.